2022
DOI: 10.1177/25168657211064232
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Wnt Signaling Pathway and ROR2 Receptor in Embryonic Development: An Update Review Article

Abstract: The Wnt family is a large class of highly conserved cysteine-rich secretory glycoproteins that play a vital role in various cellular and physiological courses through different signaling pathways during embryogenesis and tissue homeostasis 3. Wnt5a is a secreted glycoprotein that belongs to the noncanonical Wnt family and is involved in a wide range of developmental and tissue homeostasis. A growing body of evidence suggests that Wnt5a affects embryonic development, signaling through various receptors, startin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 91 publications
(112 reference statements)
0
10
0
1
Order By: Relevance
“…Tetralogy of Fallot is one of the most common congenital heart diseases developed during embryonic development. In embryonic development, successful cell‐to‐cell coordination is required to provide appropriate direction, resulting in cell proliferation, differentiation and apoptosis 9 . Right ventricular hypertrophy is a secondary process resulting from the hemodynamic overload proper of the malformation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tetralogy of Fallot is one of the most common congenital heart diseases developed during embryonic development. In embryonic development, successful cell‐to‐cell coordination is required to provide appropriate direction, resulting in cell proliferation, differentiation and apoptosis 9 . Right ventricular hypertrophy is a secondary process resulting from the hemodynamic overload proper of the malformation.…”
Section: Discussionmentioning
confidence: 99%
“…However, their role is unspecific and not limited to septum formation 25–28 . In addition, other studies have shown that ROR2 is essential for maintaining cardiomyocyte proliferation 9,29 . Besides that, ROR2 appears to play a dual role as a tumour suppressor or activator in certain types of cancer 30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Receptor tyrosine kinase‐like orphan receptor 2 (ROR2), encoding an orphan receptor tyrosine kinase, is selectively expressed in specific cell lineages, which plays critical roles in regulating cell cycle, migration, proliferation, and apoptosis as well as inflammatory responses by initiating signaling cascades. 7 , 8 ROR2 is an important receptor involved in the Wnt5a‐mediated inflammatory response in atherosclerosis 9 and PM2.5‐related chronic obstructive pulmonary disease 10 as well as the malignancies. 11 Extracellular signal‐regulated kinase (ERK) and c‐Jun N‐terminal kinase (JNK) are important regulatory proteins in the inflammatory responses of LPS‐induced ALI.…”
Section: Introductionmentioning
confidence: 99%